Traditional Uses of the Family Piperaceae in Oaxaca, Mexico. (November 2019) - Martínez-Bautista, Brian Giovanni; Bernal-Ramírez, Luis Alberto; Bravo-Avilez, David; Samain, Marie-Stéphanie; Amezcua, José Manuel Ramírez; Rendón-Aguilar, Beatriz
The ethnobotanical importance of the family Piperaceae is recognized mainly for its medicinal properties. A total of 106 species of two genera of this family ( Piper and Peperomia ) have been collected in Oaxaca, but only 18 are recorded in scientific publications as medicinal, edible, veterinary, or ritual plants. The objectives of this study are to describe the traditional knowledge and uses of the Piperaceae in areas of high biocultural diversity of Oaxaca and to analyze the relationship between its geographic distribution with ethnobotanical records among ethnic groups. Fieldwork was carried out between 2013 and 2016, and voucher specimens were reviewed in Mexican herbaria. Two multivariate analyses were applied to compare the geographic distribution of Piperaceae with ethnobotanical knowledge in Oaxaca. A total of 13 species of Peperomia, and 7 of Piper were collected, besides some unidentified species of both genera. Seven use categories were registered, with medicinal and edible being the most important. A high percentage (65%) of the species is named in at least one native language. Most species have a single use, mainly medicinal. Peperomia has been collected in Oaxaca since 1980, while Piper since 1960. Multivariate analysis indicated the existence of a differentiated ethnobotanical knowledge of this family among ethnic groups, related to the geographic distribution of species. This study evidences that ethnic groups, who maintain areas of higher biodiversity, obtain these species mainly from the wild, from specific microenvironments; hence, conservation practices must be reinforced for them, as for all ecosystems in general.